miRNA-374 Regulates Dexamethasone-induced Differentiation of Primary Cultures of Porcine Adipocytes - Pan, S.; Zheng, Y.; Zhao, R.; Yang, X. (Hormone and Metabolic Research, 2013)
To investigate the effect of glucocorticoid on adipocytes metabolism and miRNAs that may be involved in adipocyte differentiation, primary porcine preadipocytes were treated with 10−6 M dexamethasone and RU486 (a glucocorticoid receptor antagonist) for 48 h. PPAR-γ (peroxisome proliferators-activated receptor-γ), and C/EBP-β (CCTTA enhancer binding protein-β) gene and protein expression were measured. The expressions of miRNAs predicted to directly target C/EBP-β were determined, and the functions of the potential miRNAs were verified. The results showed that the triglyceride content in cultured adipocytes increased significantly after 10−6 M dexamethasone treatment for 48 h, whereas the cell viability did not differ among the four groups (Control: 10−6 M dexamethasone; 10−6 M RU486: 10−6 M dexamethasone+10−6 M RU486) (p>0.05). Cells treated with dexamethasone for 48 h significantly upregulated perilipin and PPAR-γ gene expression, and PPAR-γ protein expression was also significantly increased. However, C/EBP-β mRNA and protein expression levels were significantly decreased. Both miR-374a and miR-374b, targeting the C/EBP-β 3′-UTR (3′-untranslated region), were signiﬁcantly increased. Dual luciferase activity assay results indicated that miR-374a/b was directly recognised and bound to the 3′-UTR of C/EBP-β and thereby suppressed C/EBP-β gene expression. The present study showed that 10−6 M dexamethasone promotes lipid accumulation in primary cultures of porcine preadipocytes. PPAR-γ and C/EBP-β protein abundance showed differences after 48 h dexamethasone treatment; miR-374a/b may be involved in regulating of C/EBP-β expression. These results provide new targets for further regulation of porcine lipid metabolism.
Keywords: miRNAs; C/EBP-β; porcine adipocyte; dexamethasone